INTERPRETASI KONDISI GEOLOGI WILAYAH VULKANIK MENGGUNAKAN ANALISA CITRA SATELIT LANDSAT 8 (Daerah Studi: Gunung Penanggungan, Jawa Timur) - Bahar, Hendra (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2017)
Mount Penanggungan is one of the volcanoes that located in East Java Province, Indonesia, with the current status is a sleeping volcano. Although Mount Penanggungan is not active, it still make an interesting investigation in geological survey, especially to identify the lithological units, due that less researchers took place in Mount Penanggungan. Remote sensing imagery, such as Landsat 8 Satellite imagery series data has been used widely in geology for mapping lithology in general. Remote sensing provides information of the properties of the surface exploration targets that is potential in mapping lithological units. Remote sensing techniques are one of the standard procedures in exploration geology, due to it is high efficiency and low cost. Lithological mapping in Mount Penanggungan area is carried out by analisys Landsat 8 Satellite imagery data with image enhancement techniques, including RGB (red, green, blue) band composite, using band 5, 6, and 7, and band ratio using combination band 4/2, 5/6, dan 6/7. From Landsat 8 Satellite imagery, combines it with the results of surface geological mapping, showed that morphology are mountains, the lithological units are devided to 4 units, andesite boulder, tuf breccias, andesite lava, and andesite breccias.